Basic questions in theology /. - Pannenberg, Wolfhart, 1928-- (London : SCM, 1970)
Translated from the German "Gundfragen systematischer Theologie".
The God of hope
Includes bibliographical footnotes
Keywords: Theology, Doctrinal -- Addresses, essays, lectures